2010
DOI: 10.1159/000319317
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Silymarin as Delayed Therapy for Acetaminophen-Induced Acute Hepatic Injury

Abstract: Aim: Recently, we have demonstrated that silymarin has a comparable pharmaceutical activity as Phyllanthus urinaria extract when used to rescue mice from acetaminophen-induced acute liver injury. In the present study, we further compared the therapeutic action of silymarin with N-acetyl cysteine (commonly used in clinical practice for emergency treatments) as a rescuer in mice after administering a lethal dose of acetaminophen for 24 h. Methods: Acute liver injury was induced in the treatment groups by intrape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…FG and FRG were orally administered once a day with gavage at the dose of 50 mg/kg [3] for 8 consecutive days. SIL was orally administered at 100 mg/kg [14] in the same way as FG and FRG. As a control group, 0.3% sodium carboxymethyl cellose sodium was administered.…”
Section: Animal Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…FG and FRG were orally administered once a day with gavage at the dose of 50 mg/kg [3] for 8 consecutive days. SIL was orally administered at 100 mg/kg [14] in the same way as FG and FRG. As a control group, 0.3% sodium carboxymethyl cellose sodium was administered.…”
Section: Animal Treatmentmentioning
confidence: 99%
“…Since the protective effect of compound K against tert ‐butyl hydroperoxide‐induced liver injury was reported,[4] FG, the artificially enriched compound K content by Lactobacillus fermentation, was expected to be effective for the prevention of APAP‐induced liver injury. Therefore, we have evaluated the protective effect of FG against APAP‐induced liver injury, together with fermented‐red‐ginseng (FRG) and silymarin extracts (SIL) prepared from Silybum marianum Gearth, the latter of which contain silybin, a well‐known hepatoprotective and antitoxidant agent [14,15]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLM is composed of several flavonolignans isomers (65–80%) with small amounts of flavonoids and fatty acids (20–35%) and other polyphenolic compounds [ 9 11 ]. The main isolated and structural active component of SLM is silybin, comprising about 33% of total SLM weight, and is clinically used [ 12 , 13 ] as hepatoprotector to treat liver injuries [ 14 ]. Besides, other biological activities for SLM, such as hepatoprotective/hepatic regenerator, immunomodulator, anti-inflammatory, antioxidant, and antifibrotic activities were described [ 11 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that some medicinal plants, such as Phyllanthus urinaria ,[1112] Dioscorea alata L,[13] and Acanthopanax koreanum [14] have protective effects with regard to APAP-induced acute liver failure. As these medicinal plants are known to have antioxidative properties, we hypothesized that natsumikan may also have a protective effect on APAP-induced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%